From Connectivity to Liveability: Enhancing Urban Waterbody Accessibility through Space Syntax in Dhaka - Mouri, Fouzia Masud; Wasi, Ahmad Abdul; Nilufar, Farida (Journal of Contemporary Urban Affairs, 2025)
Urban waterbodies play a vital role in enhancing ecological sustainability, social interaction, and neighbourhood liveability, yet in rapidly urbanising contexts such as Dhaka, they are increasingly threatened by encroachment, pollution, and reduced accessibility. This study investigates the accessibility and spatial integration of two significant urban waterbodies (Dholaikhal Narinda Pond and Shahjahanpur Jheel) under the Dhaka City Neighbourhood Upgrading Project (DCNUP), which seeks to revitalise public open spaces for disadvantaged communities. Using Space Syntax analysis, the research assesses spatial configuration through measures of Connectivity (CN), Global Integration (Rn), and Local Integration (R4) to evaluate accessibility at city and neighbourhood scales. Results indicate that Dholaikhal Narinda Pond demonstrates higher connectivity and global integration values, positioning it as a potential city-scale destination capable of enhancing urban inclusivity. By contrast, Shahjahanpur Jheel, though limited in city-wide accessibility, exhibits strong local integration, highlighting its potential as a neighbourhood-scale public space. These findings underscore the importance of aligning spatial analysis with urban design strategies to enhance accessibility and maximise social benefits. The study concludes that integrating syntactic measures into early project planning can help policymakers and urban designers anticipate patterns of use and achieve more equitable and sustainable revitalisation of public waterbodies in Dhaka.